Analysis of the Effect of Financial Performance on Investment Policy in Telecommunication Companies Listed on the Indonesia Stock Exchange - Muh. Saharulla; Andi Rustam; A. Ifayani Haanurat (Return : Study of Management, Economic and Bussines, 2024)
This study aims to analyze the influence of financial performance on investment policies in telecommunication companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. In this study, four main financial ratios, namely Current Ratio (CR), Debt-to-Equity Ratio (DER), Return on Assets (ROA), and Working Capital Turnover (WCT) are used as independent variables to measure their impact on the company's investment policy. The data used is sourced from the company's annual financial statements available on the IDX. The analysis method used is multiple linear regression to see the relationship between financial variables and investment policy. The results show that the Current Ratio has no significant influence on investment policy and Return on Assets has a positive and significant influence on investment policy, while the Debt-to-Equity Ratio shows a significant positive influence. Working Capital Turnover does not have a significant influence on investment policy. This finding provides practical implications for company management in designing optimal investment policies based on the company's financial performance.